Implementasi Metode Topsis Dalam Memberikan Rekomendasi Tailor Di Kota Bengkulu - M. Endri Hardinata; Liza Yulianti; Dimas Aulia Trianggana (Jurnal Media Computer Science, 2026)
The general public requires high-quality tailoring services that are fast and within their budget. However, many consumers still struggle to choose the right tailor due to a lack of objective information about quality, price, and services offered. The implementation of the TOPSIS method in providing tailor recommendations in Bengkulu City can offer the best tailor recommendations in Bengkulu City based on consumer criteria such as price, facilities, and turnaround time, as well as provide information on each tailor in Bengkulu City, including address, contact number, operating hours, facilities, and prices. To facilitate the implementation of the TOPSIS method, a web-based application was developed using the PHP programming language with a MySQL database. The application for implementing the TOPSIS method in providing tailor recommendations in Bengkulu City can be accessed online via the URL link http://tailorkotabengkulu.online/. Based on the system testing conducted, it can be concluded that the application for implementing the TOPSIS method in providing tailor recommendations in Bengkulu City has functioned well as expected and is capable of providing tailor recommendations that align with consumer preferences.